Evaluation of nutritional properties of cassava-legumes snacks for domestic consumption: consumer acceptance and willingness to pay in Zambia - Alamu, Emmanuel Oladeji; Maziya-Dixon, Busie; Olaniyan, B.; Ntawuruhunga, P.; Chikoye, David (American Institute of Mathematical Sciences, 2020)
High-quality cassava flour (HQCF) is a cheaper alternative to wheat in the production of snacks. This study assessed the nutritional properties and consumer acceptability of cassava-legume snacks in Zambia. Cassava snacks were made from 100% HQCF, 50:50 cassava-soybean flour blend, 50:50 cassava-cowpea flour blend and 100% wheat flour as the control. The samples were analyzed for nutritional, functional and anti-nutritional properties using standard laboratory methods. Also, a well-outlined questionnaire was used to collect data on consumer preferences. The results showed a significant (P < 0.05) effect of product type on all the proximate components except starch that had no significant effect (P > 0.05). There was a significant (P < 0.05) increase in ash, protein and fat contents but a decrease in total sugars, amylose and starch contents of the legume-fortified snacks when compared with 100% cassava snacks. Cassava-legume snacks had a high acceptance in Kasama, Kaoma and Mansa districts, with a better preference for the cowpea variant of tidbit. There was a positive linear relationship between snack sensory characteristics (aroma, taste and texture) and consumer willingness-to-pay (WTP). The results show that snacks that are acceptable, affordable, nutritious and of excellent preference characteristics can be produced from cassava and legumes for households in Zambia.